Information organization and the philosophy of history. Issue 6 (23rd April 2013) - Shaw, Ryan
<x xml:space="preserve">Abstract</x> The philosophy of history can help articulate problems relevant to information organization. One such problem is "aboutness": How do texts relate to the world? In response to this problem, philosophers of history have developed theories of colligation describing how authors bind together phenomena under organizing concepts. Drawing on these ideas, I present a theory of subject analysis that avoids the problematic illusion of an independent "landscape" of subjects. This theory points to a broad vision of the future of information organization and some specific challenges to be met.